Crop capacity and quality of castor plant seeds in Poltava region - Шокало, Н. С. (Scientific Progress & Innovations, 2012)
Significant climate warming on our planet made possible to expand growing area of castor plant (valuable oil crop) (Ricinus communis L.) in Ukraine. Influence of climatic conditions upon castor plant growth in transitional south part of Poltava region is analyzed. It is established that high temperature and adequate rainfall during castor plant vegetation in experiment under seeding rate of 40000 items per hectare facilitated to forming crop capacity of nearly 15 centners per hectare. Mass of 1000 seeds was 270.2 g; oil content was more than 52 %. These indices ensured castor plant crop capacity of 7.8 centners per hectare.